Consumer Attitudes on Domestic Water-Saving Practices in Gombak District, Selangor - Afgani @ Eusoff, Yendo; M. Aminuddin, Normadihah; Puad Mat Som, Ahmad; Amin, Aziz; Abdul Ghani, Norizan (International Journal of Engineering and Technology, 2018)
Consumer attitude needs to be changed to ensure the adequacy of water supply in Malaysia due to serious issues likes rising water demands, pollution, global population growth and climate change. An existing study on domestic water consumption behaviour among Malaysians are not extensively discussed in depth, whereas the constructs of consumer behaviour should be seriously addressed in the effort to create awareness on water conservation. The paper intends to identify the level of attitude of domestic water consumers according to their cognitive, conative and affective constructs. The data was collected from five territorial divisions located in Gombak, Selangor, Malaysia through survey by using structured questionnaires to 400 domestic water users from December 2016 to February 2017. All the data were analyzed using SPSS version 21 to produce descriptive results (frequency, percentage, overall mean and standard deviation score). The findings show that the measurement level of domestic water consumers' attitudes, which were ‘cognitive’, ‘conative’ and ‘affective’, varied according to the determination of mean scores. Generally, the study output shows cognitive constructs are at a high level (4.71) while the conative constructs (3.27) and affective (3.15) are in moderate level. The existence of consumers’ attitudes at higher levels indicate that respondents are more likely to assess the use of water carefully, to reduce the wastage of water and contribute to the reduction of monthly water bill costs among households.